(untitled) - Barker, Robert L (Washington, DC, 1995)
Social work terms -- Milestones in the development of social work and social welfare; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social service -- United States -- Dictionaries; Dịch vụ xã hội -- Hoa Kỳ -- Từ điển